Philippine Country Report Welding, Metalforming and Metal Casting Sectors. - Gopez, Adolfo Jesus R. (Philippine Engineering Journal)
This paper gives a country report on the status, technology, manpower and development plans of the welding, metalforming and metal casting sectors of the Metals and Engineering Industry. Welding is used predominantly by about 1400 small scale iron works fabrication shops, 35 vehicle chassis and body markers and 13 pipe and tubemakers with an existing aggregate capacity of 300,000 mt. In metalforming, there are 25 bar rolling facilities, 8 wire rod rolling facilities and 6 structural section rolling facilities with an aggregate of 938,400 MT. There are sixty firms utilizing wire forming techniques to manufacture wire products, while only five firms offer mechanized steel forging. Smithery or hand forging is widely practiced in at least 6 regions of the country. Extrusion technology is used by five firms, while sheet metalforming is widespread in the urban communities. The country has 221 metalcasting plants but only 153 are operating. Equipment inventory in welding showed that about 60 percent are metal arc welding machines while 21 percent are oxy-acetylene welding sets. In metalforming, industry sources have estimated that 60 percent of the facilities use second hand equipment at least 20 years old. The degree of mechanization of metalcasting plants is low, with only 24 percent of the parts being partially mechanized. Manpower needs of the three sectors, according to a study by the National Manpower and Youth Council, are substantial,with about 1800 additional welders, 1700 additional mill workers, 1000 sheet metal workers needed per year up to 1993. No figures are cited for the metalcasting sector. The strength of all three sectors, and the Metals and Engineering Industry as a whole includes the existence of a large pool of trainable manpower, a large potential domestic market, and to a certain extent product acceptance in the international market. The weaknesses are lack of adequate or up to date facilities, difficulty in sourcing good quality low cost raw materials and the prevailing low productivity levels. The development plans for the three sectors are taken from the Metals and Engineering Industries National Action Plant 1990-2000, considered as a blueprint towards industrialization of the country. The plan was formulated by a multi-sectoral body composed of government officials, industry captains and members of the academe.